Human gingiva-derived mesenchymal stem cells are therapeutic in lupus nephritis through targeting of CD39−CD73 signaling pathway. Issue 113 (September 2020) - Dang, Junlong; Xu, Zhenjian; Xu, Anping; Liu, Yan; Fu, Qingling; Wang, Julie; Huang, Feng; Zheng, Yuejuan; Qi, Guangying; Sun, Boqing; Bellanti, Joseph A.; Kandalam, Umadevi; et al.
Abstract: Cell specific and cytokine targeted therapeutics have underperformed in systemic lupus erythematosus (SLE). Mesenchymal stem cells (MSCs) have emerged as a novel therapy to address the dysregulation in autoimmune diseases but also have limitations. Human gingiva derived MSCs (GMSCs) are superior in regulating immune responses. Here, we demonstrate that the adoptive transfer of GMSCs homes to and maintains in the kidney and has a robust therapeutic effect in a spontaneous lupus nephritis model. Specifically, GMSCs limits the development of autoantibodies as well as proteinuria, decreases the frequency of plasma cells and lupus nephritis histopathological scores by directly suppressing B cells activation, proliferation and differentiation. The blockage of CD39 − CD73 pathway dramatically abrogates the suppressive capacities of GMSCs in vitro and in vivo and highlights the significance of this signaling pathway in SLE. Collectively, manipulation of GMSCs provides a promising strategy for the treatment of patients with SLE and other autoimmune diseases. Highlights: GMSCs suppress B cell activation, proliferation and plasma cell differentiation in vitro and in vivo by clearing the extracellular ATP via CD39-CD73 pathway. GMSCs can home and maintain to the kidney and display a robust therapeutic effect on a spontaneous lupus nephritis model by directly targeting B cells. Administration of GMSCs or the targeting of the CD39-CD73 signaling axis may have a promising therapeutic role in patients with SLE and other autoimmune diseases.